Signal and Noise: Proton Pump Inhibitors and the Risk of Dementia?. Issue 1 (8th November 2022) - Friesen, Kevin J.; Falk, Jamie; Chateau, Dan; Kuo, I. Fan; Bugden, Shawn
Abstract : The association between proton pump inhibitor (PPI) use and dementia remains controversial. This cohort study re‐examines this issue, addressing shortcomings identified in previous publications using a population‐based and a high‐dimension propensity‐score matched cohort to follow patients for up to 22 years. Cox regression models using baseline characteristics, a lag period, and time‐varying variables were used to examine the risk of dementia by cumulative PPI exposure. High‐dose PPI users (> 180 days of use) had significantly higher risk of dementia in crude Cox models. After adjustment for medical diagnoses and prescription drug use, these associations disappeared. Among high‐dose users starting PPI therapy between 46 and 55 years old, the unadjusted hazard ratio (HR) was 1.55 (95% confidence interval (CI) 1.14, 2.10); the adjusted hazard ratio (aHR) was 1.10 (95% CI 0.80, 1.51). For high‐dose users starting therapy between 56 and 65 years, HR = 1.22 (95% CI1.03, 1.44); aHR = 0.99 (95% CI 0.83, 1.17). High‐dose users between the ages of 66 and 75 years had no association with the risk of dementia. The use of lag models or time‐varying parameters similarly found some association with dementia in crude, but not multivariable Cox models. Although high‐dose PPI users were more likely to develop dementia, they were more likely to be diagnosed with dementia risk factors, such as diabetes and cardiovascular disease, which are risk factors for dementia. Controlling for these conditions using multivariable models or a propensity‐score matched cohort eliminated this association.